CAMELS and Greek banking sector performance during the crisis an analysis and review of the evidence - Alina Hyz (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
The main objective of this study is to examine the performance of Greek banking sector and to identify the main problems and prospects of Greek banks. The analysis used the data from financial statements and statistical materials of four biggest commercial banks in Greece. The main methodology is CAMELS model. The paper is organized as follows: after the introduction, we briefly present the macroeconomic situation and the evolution of banking sector structure in Greece. This is followed by the presentation of research methodology and the data sources used in the analysis. The results are presented and discussed in next section. We conclude with study limitations and further opportunities for research.